The Analysis Study of High-intensity Focused Ultrasound in Management of Placenta Accreta Spectrum: A Comprehensive Systematic Review - Wilda Suci Hidayah; Moh Ilham Nur Baha (International Medical Journal Corp. Ltd, 2024)
Background: Placenta Accreta Spectrum (PAS) refers to a group of abnormal placental invasion disorders involving the uterine wall. High-Intensity Focused Ultrasound (HIFU) has emerged as a promising non-invasive treatment modality for PAS. This systematic review aims to evaluate the clinical outcomes associated with HIFU in the management of PAS. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: HIFU offers a promising, non-invasive alternative for managing Placenta Accreta Spectrum (PAS), preserving fertility, minimizing complications, and ensuring positive outcomes. While further research is needed, it could become a standard treatment option in obstetrics and gynecology.